Thermal performance of recycled aggregate mortar. (2014) - Nicholas, Thomas; Radford, Paul D.; Byars, Nan
When investigating the applicability of different materials for construction it is prudent to ensure that the materials used in replacement exhibit comparable performance to the natural material being replaced. This study uses a thermal conductivity analyser to determine the thermal conductivity and effusivity of standard normal weight masonry sand mortar specimens and several recycled and lightweight aggregates mortar specimens. R-values for each of the test mortars and the control mortar made with masonry sand was calculated with the control having the lowest R-value of the mortars tested. The results showed that replacing masonry sand mortar with any of the other mortars tested reduced the effect of thermal bridging through the mortar joint.